2005
DOI: 10.1101/gad.1360605
|View full text |Cite
|
Sign up to set email alerts
|

TAK1, but not TAB1 or TAB2, plays an essential role in multiple signaling pathways in vivo

Abstract: TGF-␤-activated kinase 1 (TAK1),[Keywords: JNK; NF-B; TAB1; TAB2; TAK1; TGF-␤] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
628
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(665 citation statements)
references
References 50 publications
34
628
0
Order By: Relevance
“…The link between TRAF6 and the IKK complex remains somewhat enigmatic, although a few key players are known. The kinase TAK1 (TGFb-activated kinase-1) is required for NF-kB, as well as AP-1 and extracellular signalrelated kinase (ERK), activation downstream of MyD88 Shim et al, 2005). Although it is widely accepted that ubiquitination is a key switch at this crucial step of NF-kB activation, considerable work at the molecular level remains to be done to understand how ubiquitination leads to activation.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between TRAF6 and the IKK complex remains somewhat enigmatic, although a few key players are known. The kinase TAK1 (TGFb-activated kinase-1) is required for NF-kB, as well as AP-1 and extracellular signalrelated kinase (ERK), activation downstream of MyD88 Shim et al, 2005). Although it is widely accepted that ubiquitination is a key switch at this crucial step of NF-kB activation, considerable work at the molecular level remains to be done to understand how ubiquitination leads to activation.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…Upon ubiquitination, RIP1 can bind directly to NEMO and recruit IKK independent of TRAF2 (Zhang et al, 2000). Signaling downstream of RIP1 requires TAK1 for the activation of IKK Shim et al, 2005). Whether TAK1 directly activates IKK or this process proceeds through an intermediary such as MEKK3 is not yet clear (Takaesu et al, 2003;Li et al, 2006).…”
Section: Tnf-r Superfamily Signalingmentioning
confidence: 99%
“…Activated TAK1 also phosphorylates and activates MAPKKs leading to activation of MAPKs such as ERK, p38 and JNK ( Figure 1). 6,25 NF-kB and MAPKs induce downstream expression of inflammatory cytokines and antiapoptotic proteins such as cellular FLICE-like inhibitory protein (c-FLIP) and cIAPs. 26,27 Drawing a link between TAK1 signaling and metabolism, studies have found that starvation and TRAIL induce autophagy in which TAK1 is actively involved by activating AMP-activated protein kinase and IKKs.…”
Section: Tak1 Activation and Downstream Pathwaysmentioning
confidence: 99%
“…Two main NF-kB-activating signalling pathways have been characterized and referred to as the 'classical' or 'canonical' pathway and the 'alternative' or 'non-canonical' pathway (Bonizzi and Karin, 2004). The classical pathway, which is triggered by cytokines such as tumor necrosis factor-a (TNFa), interleukin (IL)-1b, or by the ligand for the T-cell or B-cell receptor, leads to IkBa degradation and subsequent nuclear import of the p50/p65 heterodimer through a NEMO/IKKg-dependent pathway (Li and Verma, 2002;Shim et al, 2005). The alternative pathway, which is triggered by cytokines such as lymphotoxin-b (LTb), BAFF and CD40, relies on the NIK-and IKKa-mediated phosphorylation and processing of the inhibitory protein p100 into p52.…”
Section: Introductionmentioning
confidence: 99%